1994
DOI: 10.3181/00379727-205-43688
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vascular Response to Hemorrhagic Hypotension in Newborn Lambs: The Influence of Developing Anemia

Abstract: The ability of newborn animals to autoregulate cerebral blood flow (CBF) has been documented. Most studies of the cerebral vascular response to hypotension utilize hemorrhage, generally confounded with anemia. We studied the cerebral blood flow and metabolic response of chloralose and urethane anesthetized newborn lambs to regulated hypotension. Lambs (< or = 7 days old) were catheterized for radioactive microsphere determinations of CBF. The dorsal sagittal sinus was catheterized to obtain cerebral blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…It is possible for preterm infants to compensate for a low haemoglobin level by increasing cardiac output 5 23. Along with the higher cardiac output, cerebral blood flow will also increase,2426 but this increase might be absent or limited in cases of mild anaemia 27 28. In fact, our data suggest that the increase in cerebral blood flow is insufficient to compensate for the decreased oxygen transport capacity.…”
Section: Discussionmentioning
confidence: 70%
“…It is possible for preterm infants to compensate for a low haemoglobin level by increasing cardiac output 5 23. Along with the higher cardiac output, cerebral blood flow will also increase,2426 but this increase might be absent or limited in cases of mild anaemia 27 28. In fact, our data suggest that the increase in cerebral blood flow is insufficient to compensate for the decreased oxygen transport capacity.…”
Section: Discussionmentioning
confidence: 70%
“…A low Hb concentration is accompanied by a low CaO 2 and low blood viscosity, which both reduce cerebral vascular resistance and therefore increase CBF (19,44,45). However, O'Neill et al (46) showed that the CBF response to hemorrhagic hypotension was not dependent on a change in hematocrit and, presumably, viscosity. Therefore, we assume that anemia has not disturbed cerebral regulation of CBF in our study.…”
Section: Discussionmentioning
confidence: 99%